2005
DOI: 10.1099/mic.0.27734-0
|View full text |Cite
|
Sign up to set email alerts
|

The H-NS protein represses transcription of the eltAB operon, which encodes heat-labile enterotoxin in enterotoxigenic Escherichia coli, by binding to regions downstream of the promoter

Abstract: Heat-labile enterotoxin, a major virulence determinant of enterotoxigenic Escherichia coli, is encoded by the eltAB operon. To elucidate the molecular mechanism by which the heat-stable nucleoid-structural (H-NS) protein controls transcription of eltAB, the authors constructed an eltAB-lacZ transcriptional fusion and performed b-galactosidase analysis. The results showed that H-NS protein exerts fivefold repression on transcription from the eltAB promoter at 37 6C and 10-fold repression at 22 6C. Two silencer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 45 publications
4
53
1
Order By: Relevance
“…H-NS and StpA repress the expression of genes encoding the type II secretory system required for secretion of E. coli heat-labile enterotoxin (LT) [34] by inhibiting open complex formation. H-NS also represses eltAB encoding the enterotoxin itself [35]. H-NS can act synergistically as co-repressor with LRP, the leucine-responsive regulatory protein, to inhibit expression of the ribosomal RNA promoter [36], although no direct interaction between LRP and H-NS has been reported.…”
Section: Interactions Between H-ns and Other Nucleoid Proteinsmentioning
confidence: 99%
“…H-NS and StpA repress the expression of genes encoding the type II secretory system required for secretion of E. coli heat-labile enterotoxin (LT) [34] by inhibiting open complex formation. H-NS also represses eltAB encoding the enterotoxin itself [35]. H-NS can act synergistically as co-repressor with LRP, the leucine-responsive regulatory protein, to inhibit expression of the ribosomal RNA promoter [36], although no direct interaction between LRP and H-NS has been reported.…”
Section: Interactions Between H-ns and Other Nucleoid Proteinsmentioning
confidence: 99%
“…The global transcriptional regulator H-NS is known to bind to curved and AT-rich DNA sequences upstream of several defined UPEC virulence genes (85), including genes encoding toxins (86)(87)(88)(89) and autotransporter proteins (8,10,90). To investigate the effect of H-NS on vat transcription, the levels of Vat expression were compared by Western blot analysis of supernatant fractions prepared from WT CFT073, CFT073 vat, CFT073 vatX, CFT073 hns, and a CFT073 vatX hns double mutant (Fig.…”
Section: Transcription Of the Vat Gene Is Directly Repressed By H-nsmentioning
confidence: 99%
“…When interacting with DNA, H-NS initially binds to a curved, AT-rich sequence, followed by oligomerization and subsequent alteration of the DNA structure (11,41). As a repressor, H-NS can prevent the RNAP from binding to the promoter (39,49), trap RNAP at the promoter through DNA bridging (8,47), or block transcription initiation or elongation when bound to the downstream sequences of the promoters (10,25,50). It has been shown that the disruption of the repressive nucleoprotein structures mediated by H-NS requires activation signals or positively acting transcription factors (reviewed in reference 11), even though little is known about the mechanisms involved in this process.…”
mentioning
confidence: 99%